PELATIHAN DAN PEMBENTUKAN POSBINDU PENYAKIT TIDAK MENULAR (PTM) ‘AISYIYAH RANTING AMBARKETAWANG - Sulistyaningsih Sulistyaningsih; Tri Hapsari Listyaningrum (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The increasing prevalence of non-communicable diseases (NCD) poses a serious threat to development because it threatens national economic growth. The global target of non-communicable diseases is 25% reduction in death from non-communicable diseases in 2025. The results of the Basic Health Research in 2018 show that the prevalence of NCD has increased when compared to Basic health research in 2013. The leaders of the 'Aisyiyah Gamping Branch have carried out routine activities every month in each branch and also have 5 branches. One of the study material programmed is the theme of health. The activity is limited to provide for counseling from health sector speakers, there has been no implementation of Posbindu of the non-communicable diseases which can be held integrated with monthly activities. The output program are the trained cadres, NCD risk factor pocketbooks, and NCD risk factor data. The results of the program are 1) 45 cadres, trained increased attitudes towards the formation of Posbindu integrated with routine study activities, 2) NCD risk factor pocketbook used for training participants 3) the formation of Posbindu non-communicable diseases integrated with 'Aisyiyah Ambarketawang Branches; 4) non-communicable diseases risk factor data for trainees and study groups. The conclusion is that training can improve the attitude and formation of Posbindu non-communicable diseases.